Isolated Pupil-Involving Third Nerve Palsy as the First Presentation of Sarcoidosis. (October 2014) - Bansal, Shveta; Yin, Kun; Vishwanath, Mandagere; Doran, Helen; Laitt, Roger; Ansons, Alec
Abstract Neurosarcoidosis is seen in 5–15% of patients with systemic sarcoidosis. The most common cranial nerve presentations are optic neuropathy and facial nerve palsy. The authors present a case of sarcoidosis presenting with a pupil-involving third nerve palsy. The patient responded to corticosteroid therapy with resolution of investigations her cranial nerve palsy but progressed to develop cerebellar signs. This is the first documented case of a pupil-involving third nerve palsy occurring as the first presentation of neurosarcoidosis. Although typically a pupil-involving third nerve palsy necessitates urgent neuroimaging to rule out a posterior communicating artery aneurysm, it is important to recognise inflammatory causes in the differential diagnosis.